Alemtuzumab mediates the CD39+ T‐regulatory cell response via CD23+ macrophages. Issue 5 (10th February 2021) - Remez, Lital; Ganelin‐Cohen, Esther; Safina, Dina; Hellmann, Mark A; Lotan, Itay; Bosak, Noam; Buxbaum, Chen; Vaknin, Adi; Shifrin, Alla; Rozenberg, Ayal
Abstract: Alemtuzumab (ALM) effectively prevents relapses of multiple sclerosis (MS). It causes lymphocyte depletion with subsequent enhancement of the T‐regulatory cell population. Direct administration of ALM to T cells causes cytolysis. However, the T cells may be indirectly affected by monocyte‐derived cells, which are resistant to ALM cytotoxicity. We aimed to examine whether ALM modulates monocytes and whether the crosstalk between monocytes and lymphocytes previously exposed to ALM would result in anti‐inflammatory effects. The CD14 + monocytes of 10 healthy controls and 10 MS (treatment naive) patients were isolated from peripheral blood mononuclear cells (PBMCs), exposed to ALM and reintroduced to PBMCs depleted of CD14 + cells. The macrophage profile was assessed and T‐cell markers were measured. ALM promoted M2 anti‐inflammatory phenotype as noted by an increased percentage in the populations of CD23 +, CD83 + and CD163 + cells. The CD23 + cells were the most upregulated (7‐fold, P = 0.0002), and the observed effect was higher in patients with MS than in healthy subjects. ALM‐exposed macrophages increased the proportion of T‐regulatory cells, without affecting the proportion of T‐effector cells. Neutralizing the CD23 + monocytes with antibodies reversed the effect specifically on the CD4 + CD39 + T‐regulatory cell subpopulation but not on the CD4 + CD25 hi CD127 lo FOXP3 + subpopulation. ALM induces the conversion of monocytes into anti‐inflammatory macrophages, which in turn promotes T‐regulatory cell enhancement, in a CD23‐dependent manner. These findings suggest that the mechanism of action of ALM is relevant to aspects of MS pathogenesis. Abstract : Our study provides insight into mechanism of action of alemtuzumab and uncovers a new aspect of multiple sclerosis pathogenesis. This drug mediates differentiation of monocytes towards M2 anti‐inflammatory macrophages, which in turn promote T‐regulatory cells. This effect is mediated by CD23.